Association between vitamin A intake and depression among patients with heart failure - Lu Wang; Xiancheng Wang; Hongyan Su; Jing Xu (ESC Heart Failure)
Abstract Aims We aim to investigate the association between vitamin A intake and depression among patients with heart failure (HF). Methods and results In this cross‐sectional study, data of HF patients were extracted from the National Health and Nutrition Examination Survey (NHANES) 2007–2020. The independent variable was vitamin A intake, and the dependent variable was depression. Weighted univariate and multivariate logistic regression models were performed to explore the association of vitamin A intake with depression in HF patients. A total of 999 HF patients were included, with a mean age of 66.19 (0.51) years, and 566 (52.49%) were male. And 197 patients have depression. Vitamin A intake ≥731.38 mcg was associated with lower incidence of depression [odds ratio (OR) = 0.37; 95% confidence interval (CI): 0.18–0.76] in HF patients. Similarly, the relationship between high vitamin A intake and lower odds of depression were also observed in subgroups of those aged >65 years (OR = 0.16; 95% CI: 0.04–0.55), males (OR = 0.35; 95% CI: 0.14–0.86), without hypertension (OR = 0.25; 95% CI: 0.11–0.58), without diabetes (OR = 0.30; 95% CI: 0.11–0.78), with hyperlipidaemia (OR = 0.23; 95% CI: 0.09–0.64), and with chronic kidney disease (CKD) (OR = 0.32; 95% CI: 0.13–0.80). Conclusions High vitamin A intake was associated with lower odds of depression in HF patients. Appropriate vitamin A supplementation may have potential benefit to the prevention of depression in HF patients. Additional prospective large‐scale studies are required to confirm whether or not vitamin A could lead to decrease in depression symptoms.